Anesthetic Management of a Teenage Primigravida with Impending Eclampsia Undergoing Emergency Cesarean Section: A Comprehensive Case Report - Paramita Putri Hapsari; Agung Nugroho (Journal of Anesthesiology and Clinical Research, 2026)
Introduction: Impending eclampsia represents a medical emergency requiring immediate maternal delivery to prevent progression to seizures and maternal-fetal compromise. The selection of an appropriate anesthetic technique for emergency cesarean section in severely preeclamptic patients remains clinically challenging, balancing the risks and benefits of regional versus general anesthesia. Case presentation: A 19-year-old primigravida at 35 weeks and 6 days of gestation presented with frontal headache, blurred vision, and nausea. Clinical evaluation revealed new-onset hypertension (131/81 mmHg), proteinuria (+2), and mild hypokalemia (3.4 mmol/L), consistent with impending eclampsia. Emergency cesarean section was performed under subarachnoid block utilizing heavy bupivacaine 15 mg with fentanyl 25 micrograms intrathecally. Hemodynamics remained stable throughout the operative period without vasopressor requirement. A male neonate was delivered with Apgar scores of 7-8-9 and a birth weight of 1825 grams. Both mother and infant had favorable postoperative outcomes with resolution of hypertensive crisis and normal neonatal transition. Conclusion: This case demonstrates the efficacy and safety of regional anesthesia in eclamptic parturients undergoing emergency cesarean delivery. Careful patient selection, appropriate drug dosing, and vigilant hemodynamic monitoring enable successful outcomes even in this high-risk scenario.